Acid-Sensing Ion Channel 1a Is Involved in N-Methyl D-Aspartate Receptor-Dependent Long-Term Depression in the Hippocampus - Mango, D.; Nisticò, R. (Frontiers in Pharmacology, 2019)
Acid-sensing ion channels (ASICs), members of the degenerin/epithelial Na+ channel superfamily, are largely expressed in the mammalian nervous system. ASIC1a are highly permeable to Ca2+ and are involved in many physiological processes, including synaptic plasticity, learning and memory. To clarify the role of ASIC1a in synaptic transmission and plasticity, we investigated N-methyl D-aspartate (NMDA) receptor-dependent long-term depression (LTD) in the CA1 region of the hippocampus. We found that (i) ASIC1a mediates a component of ASIC1a excitatory postsynaptic currents (EPSCs); (ii) ASIC1a plays a role in electrical LTD induced by LFS protocol both in P13-18 and P30-40 animals; (iii) ASIC1a is involved in chemical LTD induced by brief bath application of NMDA both in P13-18 and P30-40 animals; and finally (iv) a functional interaction between ASIC1a and NMDA receptors occurs during LTD. These findings suggest a new role for ASIC1a channels in specific forms of synaptic plasticity in the mouse hippocampus.